ANALYTICAL METHOD DEVELOPMENT, VALIDATION AND FORCED DEGRADATION STUDIES OF LANSOPRAZOLE BY RP-HPLC - Meher, Madhavi K; Bhangale, Charushila; Dholas, Ramdas; Prashant, Vandana Aher; Pawar, Rohan (Asian Journal of Pharmaceutical Research and Development, 2018)
The objective of this work is to develop a rapid, precise, accurate and sensitive revere phase liquid chromatographic method and Forced degradation studies for the estimation of Lansoprazole. The chromatographic method was standardized for Lansoprazole using Shimadzu HPLC model reverse phase analytical Inspire grace C18 column (250 mm x 4.5 mm, 5mm particle size) with PC-3000-M Reciprocating Pump (40 Mpa) and UV-3000-M Detector, at 285nm and flow rate of 0.8 ml/min. The mobile phase consists of 80:20 Methanol: water. The linearity of proposed method was investigated in the range of 10-50 µm/ml (R2 = 0.999) of Lansoprazole. The limit of detection (LOD) was found to be 0.12 mm/ml. The limit of quantification (LOQ) was found to be 0.36 mg/ml. The retention time of Lansoprazole found to be 5.4 min. The method was statistically validated and % RSD was found to be less than 2 indicating high degree of accuracy and precision. Hence proposed method can be successfully applied for the estimation of Lansoprazole in further studies. Keywords: Lansoprazole, RP-HPLC, Chromatogram, validation, estimation.